INSTRUCTIONAL LEADERSHIP AND TEACHER SELF-EFFICACY ON JOB SATISFACTION: THE MEDIATING EFFECT OF SCHOOL CLIMATE IN INDONESIAN ISLAMIC SENIOR HIGH SCHOOLS - Ahmad Ridwan; Robi Hendra; Francisco D. Guillén-Gámez; Muhammad Fauzan; Turki Mesfer Alqhatani; Lalu Nurul Yaqin; Mohd Afifi Bahurudin Setambah (LPPM Universitas Jambi, 2024)
This study explores the impact of instructional leadership and teacher self-efficacy on job satisfaction among teachers in Indonesian Islamic Senior High Schools (Madrasah Aliyah), focusing on the mediating role of school climate. Instructional leadership plays a crucial role in shaping a positive school environment, which can enhance teacher job satisfaction by providing necessary guidance, resources, and support. A mixed-method approach was employed, with data collected from 219 teachers using validated survey instruments. The Content Validity Index (CVI) was used to ensure instrument reliability. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess relationships between variables and the mediating effect of school climate. The results show that instructional leadership significantly impacts both school climate and teacher job satisfaction, with path coefficient values of .463 and .818, respectively. However, school climate did not significantly mediate the relationship between instructional leadership and job satisfaction. Teacher self-efficacy, while positively influencing school climate (p < .05), did not have a substantial direct effect on job satisfaction (ß = -0.058). This research provides fresh insights into the nuanced interplay between leadership, teacher self-efficacy, and job satisfaction in the context of Islamic schools. The findings highlight school climate's indirect yet pivotal role in educational leadership dynamics. By integrating these variables, the study offers practical recommendations for improving leadership strategies and enhancing teacher well-being in faith-based educational settings.